Engineering graphene and TMDs based van der Waals heterostructures for photovoltaic and photoelectrochemical solar energy conversion - Li, Changli; Cao, Qi; Wang, Faze; Xiao, Yequan; Li, Yanbo; Delaunay, Jean-Jacques; Zhu, Hongwei (Chemical Society reviews, 2018)
Graphene and two-dimensional (2D) transition metal dichalcogenides (TMDs) have attracted significant interest due to their unique properties that cannot be obtained in their bulk counterparts. These atomically thin 2D materials have demonstrated strong light-matter interactions, tunable optical bandgap structures and unique structural and electrical properties, rendering possible the high conversion efficiency of solar energy with a minimal amount of active absorber material. The isolated 2D monolayer can be stacked into arbitrary van der Waals (vdWs) heterostructures without the need to consider lattice matching. Several combinations of 2D/3D and 2D/2D materials have been assembled to create vdWs heterojunctions for photovoltaic (PV) and photoelectrochemical (PEC) energy conversion. However, the complex, less-constrained, and more environmentally vulnerable interface in a vdWs heterojunction is different from that of a conventional, epitaxially grown heterojunction, engendering new challenges for surface and interface engineering. In this review, the physics of band alignment, the chemistry of surface modification and the behavior of photoexcited charge transfer at the interface during PV and PEC processes will be discussed. We will present a survey of the recent progress and challenges of 2D/3D and 2D/2D vdWs heterojunctions, with emphasis on their applicability to PV and PEC devices. Finally, we will discuss emerging issues yet to be explored for 2D materials to achieve high solar energy conversion efficiency and possible strategies to improve their performance. This review provides a systematic overview of the integration, surface, and interfacial engineering of 2D/3D and 2D/2D homo/heterojunctions for PV and PEC applications.